Feasibility and safety of left bundle branch area pacing-cardiac resynchronization therapy in elderly patients - Grieco, Domenico; Bressi, Edoardo; Sedláček, Kamil; Čurila, Karol; Vernooy, Kevin; Fedele, Elisa; De Ruvo, Ermenegildo; Fagagnini, Alessandro; Kron, Jordana; Padala, Santosh K; Ellenbogen, Kenneth A; Calò, Leonardo (Journal of interventional cardiac electrophysiology, 2023)
BACKGROUND: Left bundle branch area pacing (LBBAP) is an emerging technique to achieve cardiac resynchronization therapy (CRT), but its feasibility and safety in elderly patients with heart failure with reduced ejection fraction and left bundle branch block is hardly investigated. METHODS: We enrolled consecutive patients with an indication for CRT comparing pacing parameters and complication rates of LBBAP-CRT in elderly patients (≥ 75 years) versus younger patients (< 75 years) over a 6-month follow-up. RESULTS: LBBAP was successful in 55/60 enrolled patients (92%), among which 25(45%) were elderly. In both groups, LBBAP significantly reduced the QRS duration (elderly group: 168 ± 15 ms to 136 ± 12 ms, p < 0.0001; younger group: 166 ± 14 ms to 134 ± 11 ms, p < 0.0001) and improved LVEF (elderly group: 28 ± 5% to 40 ± 7%, p < 0.0001; younger group: 29 ± 5% to 41 ± 8%, p < 0.0001). The pacing threshold was 0.9 ± 0.8 V in the elderly group vs. 0.7 ± 0.5 V in the younger group (p = 0.350). The R wave was 9.5 ± 3.9 mV in elderly patients vs. 10.7 ± 2.7 mV in younger patients (p = 0.341). The fluoroscopic (elderly: 13 ± 7 min vs. younger: 11 ± 7 min, p = 0.153) and procedural time (elderly: 80 ± 20 min vs. younger: 78 ± 16 min, p = 0.749) were comparable between groups. Lead dislodgement occurred in 2(4%) patients, 1 in each group (p = 1.000). Intraprocedural septal perforation occurred in three patients (5%), 2(8%) in the elderly group (p = 0.585). One patient (2%) in the elderly group had a pocket infection. CONCLUSIONS: LBBAP is a feasible and safe technique for delivering physiological pacing in elderly patients who are candidates for CRT with suitable pacing parameters and low complication rates.
Keywords: výsledek terapie; Stroke Volume; Electrocardiography; Cardiac Pacing, Artificial; Cardiac resynchronization therapy; Cardiac Resynchronization Therapy; kardiostimulace umělá; Heart failure; Aged; senioři; tepový objem; Treatment Outcome; lidé; Conduction system pacing; Humans; Bundle of His; Elderly patients; srdeční resynchronizační terapie; Left bundle branch area pacing; Hisův svazek; studie proveditelnosti; elektrokardiografie; Feasibility Studies